STUDIES ON THE CULTIVATION AND INTRODUCTION OF SANDALWOOD ( SANTALVM ALBUM L) AT KARACHI, PAKISTAN 24°59'N 68°56'E (Biological Sciences - PJSIR, 2002)
Efforts were made to germin ate the seeds of Santa/um album L. (Sandalwood) for the  first  time  in  the Pakistan. The seeds germinated in about 8-16 days after the treatment of gibberellic acid to break the dormancy of the seeds. 500ppm gibberellic acid solution dose gave the opti mu m  result  and untreated  seeds gave  poor  results. The paper  encompasses the results related with the effect of irrigation on the germination of seeds and the seedling height plus the subsequent successful growth of this plant during the last 12 years. The optimum conditions for the growth of this  plant  are  discussed.